Rome II Regulation : pocket commentary - Huber, Peter, 1966- (Pocket commentaries., 2011)
HauptbeschreibungThe Rome II Regulation creates a common regime of conflict of law rules for tort, unjust enrichment, negotiorum gestio and culpa in contrahendo for (most of) the member states of the EU. This book provides an article-by-article commentary which explains the underlying concepts and suggests solutions for problems that have arisen or may arise in the application of the regulation. The book is the first volume of the new s.elp series of Pocket Commentaries on European regulations and international conventions in the area of conflict of laws. The series is meant to provide a first r.